Comparison of magnetic resonance-guided high-intensity focused ultrasound with uterine artery embolization for the treatment of uterine myoma: A systematic literature review and meta-analysis - Cherng-Jye Jeng; Cheng-Yu Long; Linus T. Chuang (Elsevier, 2020)
Objective: This study aimed to compare the outcomes of magnetic resonance-guided (MR-g) high-intensity focused ultrasound (HIFU) with uterine artery embolization (UAE) for the treatment of uterine myoma. Materials and methods: A systematic literature review and meta-analysis was conducted using database searches of Medline, Cochrane, EMBASE, and Google Scholar. Articles were searched through March 25, 2020. Outcomes of interest were Symptom Severity Score (SSS), Health-related Quality of Life (HRQoL), re-intervention rate, and rate of adverse reactions in patients with uterine myoma. Results: Four studies were included with a total of 207 patients with uterine myomas who received MR-g HIFU and 201 who received UAE. UAE was associated with a greater reduction in SSS, improved HRQoL, and a significantly lower re-intervention rate compared with MR-g HIFU in 3 of 4 included studies. No significant differences were found in the incidence and severity of adverse events between treatment arms in one study, but differences were observed in the percentage of adverse reactions in another. Conclusion: Published evidence suggests that the efficacy of MR-g HIFU may not be superior to that of UAE in the treatment of uterine myoma.